Trends, patterns, and maternal characteristics of opioid prescribing during pregnancy in a large population-based cohort study. (1st April 2022) - Nechuta, Sarah; Mukhopadhyay, Sutapa; Golladay, Molly; Rainey, Jacob; Krishnaswami, Shanthi
Abstract: Background: Opioid use during pregnancy has been associated with adverse maternal and infant health outcomes. Prescription drug monitoring programs (PDMP) provide a population-based source of prescription data. We linked statewide PDMP and birth certificate data in Tennessee (TN) to determine patterns of prescription opioid and benzodiazepine use during pregnancy. Methods: We constructed a cohort of 311, 217 live singleton births from 2013 to 2016 with prescription history from 90 days before pregnancy to birth. Descriptive statistics were used to describe opioid prescription patterns during pregnancy overall, by maternal characteristics and by year. Multivariable logistic regression models estimated adjusted odds ratios and 95% confidence intervals for factors associated with prescription use. Results: The prevalence of prescription use during pregnancy was 14.1% for opioid analgesics, 1.6% buprenorphine for medication-assisted treatment, and 2.6% for benzodiazepines. The prevalence of opioid analgesic use decreased from 16.6% (2013) to 11.8% (2016) (ptrend < 0.001). About 25% used for > 7 and 9.7% for > 30 days' supply. The most common types were hydrocodone (9.3%), codeine (3.4%), and oxycodone (2.9%). In adjusted models, lower education, lower income, pre-pregnancy obesity and smoking during pregnancy were associated with increased odds of any opioid and opioid analgesic use. Conclusion(s): Despite the encouraging trend of decreasing use of prescription opioid analgesics, the overall prevalence remained close to 12% with many women using for long durations. Use was associated with lower socioeconomic status, obesity, and prenatal smoking. Findings highlight the need for maternal education and resources, and provider support for implementation of evidence-based care. Highlights: No study has linked PDMP and birth certificate data. This can provide population-based data on prenatal opioid prescribing patterns. Prenatal opioid prescriptions decreased over time, but prevalence was still 12%. Opioid use was associated with lower education and income, obesity, and smoking.